Investigation of CZTS absorber layer deposited by spin coating technique for photovoltaic applications. (2022) - Ziti, Ahmed; Hartiti, Bouchaib; Labrim, Hicham; Doubi, Youssef; Joël Tchognia Nkuissi, Hervé; Nouria, Youssef; Fadili, Salah; Batan, Abdelkrim; Tahri, Mounia; Ridah, Abderraouf; Thevenin, Philippe
Abstract: In this work we prepared and deposited Cu2 ZnSnS4 (CZTS) absorber layers by sol gel spin coating technique on ordinary glass substrates. We studied the influence of annealing time on structural, compositional, morphological, optical and electrical properties of films at different times of 5, 10 and 20 min, respectively. The films have been analyzed by different characterization techniques such as X-ray diffractometer (XRD), Raman spectroscopy, scanning electron microscopy (SEM), energy dispersive X-ray spectroscopy (EDS), UV–visible-NIR spectrophotometer and four point probe method. XRD patterns showed pure kesterite CZTS with preferential orientation along (1 1 2) plane and calculated lattice parameters a = b = 0.5428 nm and c = 1.0849 nm. Raman scattering measurements confirmed the existence of a single CZTS phase showing a single peak at 338 cm −1 . SEM images showed compact, uniform and densely surface morphology. EDS analysis indicated near-stoichiometric CZTS films, UV–Visible-NIR spectrophotometer showed that the optical band gap energy of CZTS thin films is found to be between 1.48 and 1.7 eV. Four point probe measurements exhibited a suitable electrical conductivity in the range 3.03–3.44 (Ω.cm) −1 . These properties make the as-synthesized CZTS films an appropriate material as absorber layer in solar cells applications.